2020
DOI: 10.36941/jesr-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Social and Emotional Challenges Encounter Jordanian Parents of Children with Autism Spectrum Disorder

Abstract: The current study aims to identify daily social and emotional challenges encountered by parents of children with Autism Spectrum Disorder (ASD) and its relation to some demographic variables. The study sample consists of 223 parents whose children having a diagnosis of ASD and receiving services at special education institutions in Amman, the capital city of Jordan. A validated scale was developed to measure social and emotional challenges. Findings revealed that while the most common social challenges were la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Physical health problems were reported in two studies (Al-qahtani, 2018 ; Shattnawi et al, 2021 ). Five studies reported social burden among parents of children with ASD (Al-qahtani, 2018 ; Gobrial, 2018 ; Alenazi et al, 2020 ; Al-Masa'deh et al, 2020 ; Shattnawi et al, 2021 ), while four studies reported psychological burden (Dababnah and Parish, 2013 ; Al-Ansari and Jahrami, 2018 ; Al-qahtani, 2018 ; Shattnawi et al, 2021 ). Parents of children with ASD reported financial burden in three of the studies (Dababnah and Parish, 2013 ; Al-qahtani, 2018 ; Shattnawi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical health problems were reported in two studies (Al-qahtani, 2018 ; Shattnawi et al, 2021 ). Five studies reported social burden among parents of children with ASD (Al-qahtani, 2018 ; Gobrial, 2018 ; Alenazi et al, 2020 ; Al-Masa'deh et al, 2020 ; Shattnawi et al, 2021 ), while four studies reported psychological burden (Dababnah and Parish, 2013 ; Al-Ansari and Jahrami, 2018 ; Al-qahtani, 2018 ; Shattnawi et al, 2021 ). Parents of children with ASD reported financial burden in three of the studies (Dababnah and Parish, 2013 ; Al-qahtani, 2018 ; Shattnawi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Factors associated with psychological disorders and the burden experienced by parents of children with ASD were explored in some of the studies. These studies found that several factors were associated with the impact of ASD on parents, including the severity of ASD, social support, economic status, maternal education, financial hardship, marital status, parental age, and the gender of the child (Al-Kandari et al, 2017 ; Alnazly and Abojedi, 2019 ; Alshekaili et al, 2019 ; Al-Masa'deh et al, 2020 ; Alshahrani and Algashmari, 2021 ; Khusaifan and El Keshky, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Jamison et al (2017) found that the family peer advocate (FPA) model significantly increased knowledge about ASD and reduced stress for caregivers [ 43 ]. Peer support interventions can positively reflect their parenting confidence, mental health, and ability to care for and provide for the whole family [ 40 , 44 , 45 ]. Community-level interventions are necessary to raise awareness and improve the perception of autism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effects of music on children's emotional development have been systematically reviewed, highlighting the potential of music as a tool for enhancing emotional intelligence (Magraner et al, 2021). Similarly, the emotional challenges encountered by parents of children with autism spectrum disorder have been investigated, emphasizing the need for support and intervention strategies in this context (al-Masa'deh et al, 2020).…”
Section: Challenges and Disordersmentioning
confidence: 99%